Zinc, magnesium and NMDA receptor alterations in the hippocampus of suicide victims - Sowa-Kućma, Magdalena; Szewczyk, Bernadeta; Sadlik, Krystyna; Piekoszewski, Wojciech; Trela, Franciszek; Opoka, Włodzimierz; Poleszak, Ewa; Pilc, Andrzej; Nowak, Gabriel (Journal of affective disorders, 2013)
There is evidence for an association between suicidal behavior and depression. Accumulating data suggests that depression is related to a dysfunction of the brain's glutamatergic system, and that the N-methyl-d-aspartate (NMDA) receptor plays an important role in antidepressant activity. Zinc and magnesium, the potent antagonists of the NMDA receptor complex, are involved in the pathophysiology of depression and exhibit antidepressant activity. The present study investigated the potency of Zn2+ and Mg2+ to [3H] MK-801, which binds to the NMDA receptor channel in the hippocampus of suicide victims (n=17) and sudden death controls (n=6). Moreover, the concentrations of zinc and magnesium (by flame atomic absorption spectrometry) and levels of NMDA subunits (NR2A and NR2B) and PSD-95 protein (by Western blotting) were determined. Our results revealed that there was a statistically significant decrease (by 29% and 40%) in the potency of zinc and magnesium (respectively) to inhibit [3H] MK-801 binding to NMDA receptors in the hippocampus in suicide tissue relative to the controls. These alterations were associated with increased NR2A (+68%) and decreases in both the NR2B (−46%) and PSD-95 (−35%) levels. Furthermore, lower concentrations (−9%) of magnesium (although not of zinc) were demonstrated in suicide tissue. Our findings indicate that alterations in the zinc, magnesium and NMDA receptor complex in the hippocampus are potentially involved in the pathophysiology of suicide-related disorders (depression), which may lead to functional NMDA receptor hyperactivity.